B lymphocytes limit senescence‐driven fibrosis resolution and favor hepatocarcinogenesis in mouse liver injury. Issue 5 (25th March 2018) - Faggioli, Francesca; Palagano, Eleonora; Di Tommaso, Luca; Donadon, Matteo; Marrella, Veronica; Recordati, Camilla; Mantero, Stefano; Villa, Anna; Vezzoni, Paolo; Cassani, Barbara
Abstract : Hepatocellular carcinoma (HCC) is a frequent neoplasia and a leading cause of inflammation‐related cancer mortality. Despite that most HCCs arise from persistent inflammatory conditions, pathways linking chronic inflammation to cancer development are still incompletely elucidated. We dissected the role of adaptive immunity in the Mdr2 knockout ( Mdr2 –/– ) mouse, a model of inflammation‐associated cancer, in which ablation of adaptive immunity has been induced genetically ( Rag2 –/– Mdr2 –/– and μMt‐Mdr2 –/– mice) or with in vivo treatments using lymphocyte‐specific depleting antibodies (anti‐CD20 or anti‐CD4/CD8). We found that activated B and T lymphocytes, secreting fibrogenic tumor necrosis factor alpha (TNFα) and other proinflammatory cytokines, infiltrated liver of the Mdr2 –/– mice during chronic fibrosing cholangitis. Lymphocyte ablation, in the Rag2 –/– Mdr2 –/– and μMt‐Mdr2 –/– mice, strongly suppressed hepatic stellate cell (HSC) activation and extracellular matrix deposition, enhancing HSC transition to cellular senescence. Moreover, lack of lymphocytes changed the intrahepatic metabolic/oxidative state, resulting in skewed macrophage polarization toward an anti‐inflammatory M2 phenotype. Remarkably, hepatocarcinogenesis was significantly suppressed in the Rag2 –/– Mdr2 –/– mice, correlating with reduced TNFα/NF‐κB (nuclear factor kappa B) pathway activation. Ablation of CD20 + B cells, but not of CD4 + /CD8 + T cells, in Mdr2 –/– mice, promoted senescence‐mediated fibrosis resolution and inhibited the protumorigenic TNFα/NF‐κB pathway. Interestingly, presence of infiltrating B cells correlated with increased tumor aggressiveness and reduced disease‐free survival in human HCC. Conclusion: Adaptive immunity sustains liver fibrosis (LF) and favors HCC growth in chronic injury, by modulating innate components of inflammation and limiting the extent of HSC senescence. Therapies designed for B‐cell targeting may be an effective strategy in LF. (Hepatology 2018;67:1970‐1985).